Effects of Zingiber officinale Powder on Semen Characteristic and Blood Serum Sex Hormones Concentration in Broilers Breeder Male - Shanoon , A.K. (International Journal of Poultry Science, 2011)
This study was conducted to examine the effects of Zingiber officinale (ginger) powder on male broiler reproductive system. Zingiber officinale was administered in the feed of two groups of male broiler breeder (30 wk age) at levels of 5 and 10 kg/ton, Third group was a control group (no additive). Treatments were ejaculate volume, sperm concentration, counts, movements, motility and abnormality, blood serum LH, FSH and testosterone concentration. The ginger caused a significant increase (p<0.05) in ejaculate volume, sperm concentration, counts, movements and a significant decrease (p<0.05) in motility and abnormality. There was also a significant increase (p<0.05) in blood serum LH, FSH and testosterone levels. Our results indicated that Zingiber officinale powder possesses pro-fertility properties in male broiler which might be a product of androgenic activities.